2015
DOI: 10.3389/fnhum.2015.00079
|View full text |Cite
|
Sign up to set email alerts
|

Attachment classification, psychophysiology and frontal EEG asymmetry across the lifespan: a review

Abstract: In recent years research on physiological response and frontal electroencephalographic (EEG) asymmetry in different patterns of infant and adult attachment has increased. We review research findings regarding associations between attachment classifications and frontal EEG asymmetry, the autonomic nervous system (ANS) and the hypothalamic-pituitary-adrenocortical axis (HPA). Studies indicate that insecure attachment is related to a heightened adrenocortical activity, heart rate and skin conductance in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 117 publications
(141 reference statements)
8
76
0
1
Order By: Relevance
“…Some researchers even argue that the attachment system is in itself a device of emotion regulation (Vrtička and Vuilleumier, 2012). Studies indicate that, in response to stress, the insecure attachment is related to a heightened adrenocortical activity, heart rate and skin conductance, which is consistent with the hypothesis that attachment insecurity leads to deficits in emotion regulation (Gander and Buchheim, 2015). The majority of neurophysiological studies of adult attachment use self-report measures (Carpenter and Kirkpatrick, 1996; Kim, 2006; Laurent and Powers, 2007; Rochman et al, 2008; Kiss et al, 2011; Dan and Raz, 2012).…”
Section: Introductionsupporting
confidence: 78%
“…Some researchers even argue that the attachment system is in itself a device of emotion regulation (Vrtička and Vuilleumier, 2012). Studies indicate that, in response to stress, the insecure attachment is related to a heightened adrenocortical activity, heart rate and skin conductance, which is consistent with the hypothesis that attachment insecurity leads to deficits in emotion regulation (Gander and Buchheim, 2015). The majority of neurophysiological studies of adult attachment use self-report measures (Carpenter and Kirkpatrick, 1996; Kim, 2006; Laurent and Powers, 2007; Rochman et al, 2008; Kiss et al, 2011; Dan and Raz, 2012).…”
Section: Introductionsupporting
confidence: 78%
“…In sum, these findings, together with numerous other studies provide strong evidence that patterns of attachment account for variability in adolescents’ and adults’ emotion regulation strategies on both a behavioral as well as a psycho-biological level (also see Spangler and Zimmermann, 1999; Gander and Buchheim, 2015). …”
Section: Introductionsupporting
confidence: 65%
“…For example, analyzing ERP responses to infant emotional faces studies using narrative measures of attachment found neural correlates associated with attentional processing (i.e., N200, P3) to be less prominent in insecure mothers (Fraedrich et al, 2010; Leyh et al, 2016a). Accordingly, studies using self-report measures of attachment found decreased ERP amplitudes in response to emotional faces in avoidant subjects (Zhang et al, 2008), as well as a response bias in favor of positive stimuli (Chavis and Kisley, 2012), while others found insecurely attached individuals to be less able to accurately discriminate between different facial emotion expressions on a neurophysiological level (Escobar et al, 2013; for a review also see Gander and Buchheim, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In order to maintain organization within the attachment system, emotional reactivity is then regulated within the central nervous system (Bretherton, 1993; Main, 1995). Over the decades, psychobiological attachment research with infants and adults has increased dramatically (Coan, 2008; Gander and Buchheim, 2015). Attachment patterns have been linked to different ways to emotion regulation processes and some researchers even argued that the attachment system is in itself an emotion regulation device (Vrtička and Vuilleumier, 2012).…”
Section: Introductionmentioning
confidence: 99%